Pembuatan Pupuk Organik Cair Fermentasi dari Urin Sapi (Ferunsa) dengan Variasi Penambahan Limbah Darah Sapi Terhadap Kualitas Pupuk Organik Cair - Hery Purnomo, Mawardi, (Teknis, 2015)
RPH (The cattle slaughter house) produces wastes, such as feses, urine, and blood of cow. The wastes are released to environment, make the evironment contamined. That waste has a potential usage for making liquid manure, after having fermentation process for a specified time. It is a research, studies ofÂ liquid organic manure that made fromÂ fermentation process of urine of cow (ferunsa) with varies addition of blood powder of cow, fucused in itâs quality. The research is conducted in 6 of treatments by adding blood powder of cow (TDS)Â as follows : 0 grame, 20 grames, 40 grames, 60 grames, 80 grames and 100 grames, for 14 daies fermentations. The results, that in level of 80 grames addition is theÂ effective treatment by the contents of C-organic, Nitrogen, Phosfor, andÂ Kalium respectively are : 6,92%, 3,53%, 4,33%, and 5,02%.Keywords: liquid organic manure, fermentation, urine of cow, blood powder of cow.